Evaluation of gingival crevicular fluid levels of tissue plasminogen activator, plasminogen activator inhibitor 2, matrix metalloproteinase-3 and interleukin 1-β in patients with different periodontal diseases - Toyman, U.; Tüter, G.; Kurtiş, B.; Kıvrak, E.; Bozkurt, Ş.; Yücel, A. A.; Serdar, M. (Journal of periodontal research, 2015)
Objectives The purpose of this study was to evaluate the gingival crevicular fluid levels of interleukin‐1beta (IL‐1β), matrix metalloproteinases‐3 (MMP‐3), tissue type plasminogen activator (t‐PA) and plasminogen activator inhibitor 2 (PAI‐2) in patients with chronic periodontitis, aggressive periodontitis (AgP) and healthy individuals (controls). Material and Methods Systemically healthy (21 chronic periodontitis, 23 AgP and 20 controls) subjects were included in this study. Plaque index, gingival index, probing pocket depth and clinical attachment level were recorded and gingival crevicular fluid samples were collected. Assays for IL‐1β, MMP‐3, t‐PA and PAI‐2 levels in gingival crevicular fluid were carried out by an enzyme‐linked immunosorbent assay. The one‐sample Kolmogorov–Smirnov test, Mann–Whitney U test and Spearman correlation coefficient were used for data analyses. Results Gingival crevicular fluid levels of t‐PA and IL‐1β were significantly higher in chronic periodontitis and AgP groups than in the control group (p < 0.001). MMP‐3 levels in gingival crevicular fluid were detected as significantly higher in the chronic periodontitis and AgP groups compared with the control group (p < 0.05). The t‐PA/PAI‐2 rate of patients with chronic periodontitis and AgP were significantly higher than the control group (p < 0.05). The positive correlations were found among the PAI‐2, t‐PA, IL‐1β and MMP‐3 levels in gingival crevicular fluid. The volume of the gingival crevicular fluid correlated with all of the clinical parameters (p < 0.001). There were positive correlations between the gingival crevicular fluid levels of PAI‐2 and the probing pocket depth and between gingival crevicular fluid levels of PAI‐2 and the clinical attachment level (p < 0.01). Similarly, significant correlations were found between t‐PA levels and probing pocket depth and between t‐PA levels and clinical attachment level measurements (p < 0.001). Conclusion The present data showed that gingival crevicular fluid levels of IL‐1 β, MMP‐3 and t‐PA increased in periodontal disease regardless of the periodontitis type and played a part in tissue destruction.